The Importance of the Dimensions of the Innovation Management in Evaluating the Innovation Capability of the Firms in the Machine Building Industry in Romania. (2016) - Alexe, Cătălin-George; Alexe, Cătălina-Monica
Abstract: Among the advantages proposed by different methods of evaluating the innovation capability based on scores are the allowing of the comparison of a company's innovation capacity, materialized at the time of the analysis in a score, with the scores of other companies. It appears necessary to delimit the importance at the level of the determinants of the innovation depending on the membership of a particular industry. Based on the literature and on our own experience, it will be identified a number of dimensions of innovation, that provides a complete image of the innovation management. Within the research more companies in the machine building industry will be involved, and determining the importance given to the dimensions of the innovation in this industry contribute to the possibility of achieving the analyzes of benchmarking on the innovation management among various companies in other industries, in this case, the IT&C industry.